(untitled) (Vietnam Journal of Community Medicine, 2021)
Objectives: Describe the rate of diabetes by rapid detection on elderly in some communes of Thai Nguyen city. Materials and Methods: A cross-sectional study had been conducted on 520 elderly. Results: The rate of diabetes in the elderly in the 7 studied communes is 23.6%, of which 12.1% is new discovery through rapid test. The proportion of subjects with pre-diabetes accounts for 19.5%, of which 8.3% are fasting blood glucose disorders and 11.2% are impaired glucose tolerance. The highest prevalence of diabetes is found in the age group 60-69 (26.6%); in which, Tich Luong ward has the highest rate of diabetic subjects (32.8%) and Linh Son commune has the lowest rate of diabetic subjects (15.4%). There were 417 subjects (80.19%) that complied with the required fasting time with the highest blood sugar test result of 16.3 mmol /l, of which 35.5% of subjects who fasted for 8 hours or more had blood glucose test ≥7 mmol /l. As a result, adding a glucose tolerance test revealed 13 more subjects (accounting for 11.4%) with diabetes. Conclusion: It is necessary to apply the rapid testing for blood sugar to all at-risk subjects, elderly in community.